PELATIHAN DETEKSI SEDERHANA BORAKS DAN FORMALIN PADA MAKANAN MENGGUNAKAN INDIKATOR ALAMI EKSTRAK KUNYIT (CURCUMA LONGA LINN) DAN INDIKATOR BUATAN - Sulistiyorini, Desy (Fakultas Teknik, Universitas Samudra, 2024)
The low awareness of small food traders regarding food safety is a health problem in Indonesia. There is still widespread use of dangerous preservatives like borax and formaldehyde, which are not meant for food. It is crucial for the community to play a role in monitoring the presence of these preservatives in food. However, conducting laboratory tests requires a significant amount of money. Thus, the objective of this community service is to educate the public about the harmful chemicals used as food preservatives and teach them how to create simple detection tools for borax and formaldehyde using inexpensive and easily accessible materials. Turmeric and a formalin testing kit are among the materials used. The food samples that were analyzed during this activity included gendar crackers, meatballs, salted fish, salted squid, white tofu, yellow tofu, and wet noodles. As a result of this service, the public becomes informed about the dangerous chemicals still being used as preservatives and gains the ability to identify borax and formaldehyde in food using natural indicators.